Flow Cytometry-based Detection of B-cell Lymphoproliferative Disorders in Patients with Mycosis Fungoides - Shamir Geller; Sigi Kay; Eran Ellenbogen; Tomer Goldsmith; Shoshi Bar-On; Emily Warshauer; Varda Deutsch; Eli Sprecher; Chava Perry; Ilan Goldberg (Medical Journals Sweden, 2020)
Abstract is missing (Short communication)